Hidden Metabolic Disturbances in Women with Normal Glucose Tolerance Five Years after Gestational Diabetes. (22nd March 2015) - Winhofer, Yvonne; Tura, Andrea; Thomas, Anita; Prikoszovich, Thomas; Winzer, Christine; Pacini, Giovanni; Luger, Anton; Kautzky-Willer, Alexandra
Abstract : Background . The study aimed to assess whether women with prior gestational diabetes (pGDM), despite maintenance of normal glucose tolerance (NGT) five years after delivery, display metabolic disturbances compared to healthy controls. Methods . 45 pGDM with NGT were compared to 18 women without a history of GDM (CON), matched for age (37.0 ± 4.1 versus 35.2 ± 5.3, P = ns ) and BMI (24.3 ± 3.1 versus 23.3 ± 3.3, P = ns ). Metabolic parameters were derived from oral and intravenous glucose tolerance tests; furthermore lipid profile, C-reactive protein (CRP), adiponectin, leptin, and glucagon were assessed. Results . Five years postpartum, pGDM had increased glucose concentrations during the OGTT (AUC: 1.12 ± 0.15 versus 1.0 ± 0.12 mol/L* min, P = 0.003 ) and insulin sensitivity was decreased compared to CON (OGIS: 467.2 ± 64.1 versus 510.6 ± 53.1 mL/min* m 2, P = 0.01 ). pGDM had lower adiponectin (8.1 ± 2.6 versus 12.6 ± 5.3, P < 0.008 ) but increased waist circumference and CRP compared to CON. Conclusions . Despite diagnosis of normal glucose tolerance, pGDM are characterized by hyperglycemia and insulin resistance compared to healthy controls, accompanied by decreased adiponectin and increased CRP concentrations, thus linking metabolic disturbances to an increased cardiovascular risk in pGDM.